A gas chromatography method for the determination of ethanol in hand sanitizing gel - Ulloa Esquivel , Tammy (2025)
The commercialization of ethanol-based hand sanitizers requires strict quality control regarding the alcohol content present in the product, which demands the application of reliable analytical laboratory methodologies to ensure accuracy and credibility of the results. The objective of this study was to develop a chromatographic method for the quantification of ethanol in commercially available hand sanitizing gels. Several tests were performed using gas chromatography with a flame ionization detector and a polyethylene glycol column, making the necessary adjustments and evaluating the main performance parameters of the method in accordance with established validation guidelines. The results demonstrated that the chromatographic method meets the acceptance criteria for key performance parameters such as linearity, repeatability, intermediate precision, and accuracy, thereby ensuring the reliability of the obtained results and the safety of the product for consumer health.